An empirical examination of stigma toward mental health problems and psychotherapy use in Veterans and active duty service members. Issue 4 (4th July 2019) - Goode, Jonathan; Swift, Joshua K.
ABSTRACT: Although many Veterans and active duty service members experience mental health problems, most do not seek out any sort of mental health help. Stigma (a significant predictor of treatment-seeking) has been documented among Veterans and active duty service members; however, previous research on stigma in these groups has primarily utilized correlational and qualitative designs. The purpose of this study was to gain a better understanding of stigma toward mental health problems in Veterans and active duty service members using an experimental design. One hundred sixty-five Veterans and active duty service members were randomized to read a vignette that described a Veteran who either did or did not experience a mental health problem and did or did not seek psychotherapy. Results indicated that the participants held more stigmatizing attitudes toward the Veteran who was described as having a mental health problem, but not toward the Veteran who was described as seeking psychotherapy. Additionally, participants held more positive attitudes toward the Veteran, compared to the attitudes that they believed other military members would hold. Last, with this sample of Veterans and active duty service members, self-stigma toward seeking psychotherapy was found to partially mediate the relationship between perceived public stigma and attitudes. Implications for addressing stigma in military service members and Veterans are discussed.